2013
DOI: 10.1186/1472-6807-13-s1-s4
|View full text |Cite
|
Sign up to set email alerts
|

A population-based evolutionary search approach to the multiple minima problem in de novo protein structure prediction

Abstract: BackgroundElucidating the native structure of a protein molecule from its sequence of amino acids, a problem known as de novo structure prediction, is a long standing challenge in computational structural biology. Difficulties in silico arise due to the high dimensionality of the protein conformational space and the ruggedness of the associated energy surface. The issue of multiple minima is a particularly troublesome hallmark of energy surfaces probed with current energy functions. In contrast to the true ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 61 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…An evolutionary algorithm employing crossover and mutation operators in a fragment-assembly context has also been described (Olson et al, 2013). Saleh et al (2013) also describe the use of evolutionary and memetic algorithms involving fragment assembly, and show that the memetic algorithm can reduce the likelihood of deep descent into local optima on the energy landscape, which is known to be detrimental to predictive accuracy (Molloy et al, 2013), and has been an issue for some of the above approaches. Owing to inaccuracies in typical low-resolution scoring functions, some first methods have now started to consider structural diversity at strategic points during the search, e.g.…”
Section: Recent Approaches To Improving Conformational Searchmentioning
confidence: 99%
“…An evolutionary algorithm employing crossover and mutation operators in a fragment-assembly context has also been described (Olson et al, 2013). Saleh et al (2013) also describe the use of evolutionary and memetic algorithms involving fragment assembly, and show that the memetic algorithm can reduce the likelihood of deep descent into local optima on the energy landscape, which is known to be detrimental to predictive accuracy (Molloy et al, 2013), and has been an issue for some of the above approaches. Owing to inaccuracies in typical low-resolution scoring functions, some first methods have now started to consider structural diversity at strategic points during the search, e.g.…”
Section: Recent Approaches To Improving Conformational Searchmentioning
confidence: 99%
“…The incorporation of domain-specific insight even to basic EAs such as basin hopping (BH) has been shown to result in competitive decoy sampling algorithms [23,28] (BH has been shown effective even in other structure modeling settings beyond template-free structure prediction [25]). Our initial comparison of BH with population-based EAs in [31,32] indicated that population-based EAs have higher exploration capability and prompted the further pursuit of population-based EAs in our work.…”
Section: Resultsmentioning
confidence: 98%
“…Studies applying EAs for decoy sampling are thus limited to very small proteins or toy models; currently, EAs are not competitive against state-of-the-art methods in template-free structure prediction. In recent work we have provided a pathway for employing EAs in template-free structure prediction by incorporating coarse-grained representations and molecular fragment replacement, improving the exploration capability of single-trajectory or population-based EAs [24,28,29,32] as well as tree-based search algorithms [26,33]. In this paper we build upon this foundation and propose a more powerful novel evolutionary search algorithm.…”
Section: Introductionmentioning
confidence: 95%
“…Our ongoing work is focusing on obtaining more information about the predictive capability of the method in a larger setting of dimeric assemblies covering diverse functional classes. Future work will additionally consider enhancing the sampling capability of the search algorithm with evolutionary search techniques investigated and tested by us in the related problem of tertiary structure prediction in proteins [47,48,51,52]. The model score may also be combined with terms of a physics-based energy function to conduct the search on a combined potentially less rugged surface.…”
Section: Resultsmentioning
confidence: 98%